Hysteresis in Regional Unemployment Rates in China - Chen, Yiyi (2022)
Unemployment is one of the most important reasons affecting people's lives and the country's economic development. Unemployment rate is an important piece in macroeconomic studies. Unemployment hysteresis refers to the fact that unemployment rate, which decreases rapidly due to economic recession, cannot rise to its original level even after economic recovery, and does not decrease significantly with the high growth phase of the economy, but remains at a high level of unemployment and persists for a long time. This paper explores whether the phenomenon of unemployment hysteresis exists in 15 regions of China from 2000 to 2020. The definition of unemployment hysteresis is introduced, the connection between unemployment hysteresis and the natural rate of unemployment is analyzed, and the causes of unemployment hysteresis are generated. An empirical analysis is made to test the unemployment hysteresis hypothesis around the unit root test for the stationarity of the time series. The non-stationarity of the time series with the presence of unit roots indicates the existence of unemployment hysteresis.